INFLATION IN HIGHER EDUCATION - Riesman, David (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1970)
If one reads about the plight of our mental hospitals, our prisons, our inadequate welfare, and our other generally-starved public services, one sees that, by contrast, higher education has been the secular cathedral of our time. However, all such institutions are "service industries," and one characteristic of service industries is that with more resources, production does not necessarily rise; it may even fall. Indeed in general, as academic salaries have risen, teaching loads have dropped (which of course does not necessarily mean that less work is being done). While the boom market for Ph.D.’s may be levelling off in the United States (if not in Canada), academic institutions have had to offer increasing amenities to Ph.D’s in shortage fields in order to recruit and retain them.